Identification of the Fanconi Anemia Complementation Group I Gene, FANCI - Josephine C. Dorsman; Marieke Levitus; Davy Rockx; Martin A. Rooimans; Anneke B. Oostra; Anneke Haitjema; Sietske T. Bakker; Jûrgen Steltenpool; Dezsö Schuler; Sheila Mohan; Detlev Schindler; Fré Arwert; et al. (Cellular Oncology)
To identify the gene underlying Fanconi anemia (FA) complementation group I we studied informative FA-I families by a genome-wide linkage analysis, which resulted in 4 candidate regions together encompassing 351 genes. Candidates were selected via bioinformatics and data mining on the basis of their resemblance to other FA genes/proteins acting in the FA pathway, such as: degree of evolutionary conservation, presence of nuclear localization signals and pattern of tissue-dependent expression. We found a candidate, KIAA1794 on chromosome 15q25-26, to be mutated in 8 affected individuals previously assigned to complementation group I. Western blots of endogenous FANCI indicated that functionally active KIAA1794 protein is lacking in FA-I individuals. Knock-down of KIAA1794 expression by siRNA in HeLa cells caused excessive chromosomal breakage induced by mitomycin C, a hallmark of FA cells. Furthermore, phenotypic reversion of a patient-derived cell line was associated with a secondary genetic alteration at the KIAA1794 locus. These data add up to two conclusions. First, KIAA1794 is a FA gene. Second, this gene is identical to FANCI, since the patient cell lines found mutated in this study included the reference cell line for group I, EUFA592.